Uganda : Request for Disbursement under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report ;, 2020)
This paper analyzes Uganda's Request for Disbursement Under the Rapid Credit Facility. The Ugandan economy is severely affected by the coronavirus disease 2019 (COVID-19) pandemic. In order to contain the impact of the pandemic, the authorities have increased health spending, strengthened social protection to the most vulnerable, and enhanced their support to the private sector. The Bank of Uganda has appropriately reduced interest rates and provided liquidity to safeguard financial stability, while maintaining exchange rate flexibility. The weakening economic conditions emanating from the Covid-19 pandemic have put significant pressures on revenue collection, expenditure, reserves and the exchange rate, creating urgent large external and fiscal financing needs. The IMF continues to monitor Uganda's situation closely and stands ready to provide policy advice and further support as needed. The authorities have also committed to put in place targeted transparency and accountability measures to ensure the appropriate use of emergency financing. The IMF's emergency financial support under the RCF, along with the additional donor financing it is expected to help catalyze, will help address Uganda's urgent balance of payments and budget support needs.